SISTEM INFORMASI PENGOLAHAN DATA RUMAH KOS MENGGUNAKAN FRAMEWORK CODEIGNITER DI KELURAHAN DEMANGAN KECAMATAN GONDOKUSUMAN YOGYAKARTA - Saputro, Guridno Adi; Hamzah, Amir; Triyono, Joko (Jurnal Script, 2013)
ABSTRACT Information systems is that information technology is growing so rapidly. Technologies that can help more easily, quickly, safely and effectively clear it is helpful to anyone who use it. Including to assist students in the boarding house search. While conducting a study / lecture will need a boarding house is important, since the students who undertake studies in a long time and needed a place to stay in the area. And it makes the issue of how students can find suitable boarding house, given some constraints such as do not know the area, or do not have friends who can demonstrate appropriate boarding house for students. This information systems which will facilitate for students who feel confused in finding suitable boarding houses and rooming will assist owners in his boarding house online marketing. The system is focused in finding the appropriate criteria to boarding reservations for a dorm room can be done with this system. Success in implementing this system is that it can work well to help students in the search for an appropriate location rooming house. Of search, directions, up to ordering online and the response of the system facilities using SMS (Short Message Service) to the owner of the boarding house that facilitate the ordering process. Keywords: Information System, Boarding House, GIS, SMS Gateway